Association between empathy and assertiveness of undergraduate students of medical colleges of Punjab - Fatima, Fozia; Siddiqui, Fuad Ahmad; Ali, Sabir; Fatima, Safia; Zahoor, Asiya; Alvi, Alina (Frontiers in Psychiatry, 2025)
The study explores the relationship between empathy and assertiveness among undergraduate medical students in Punjab, Pakistan. Empathy, critical for patient care, enhances understanding and communication, while assertiveness is vital for advocacy and effective decision-making. Conducted as a cross-sectional analysis with 104 students from two medical colleges, the study used the Jefferson Scale of Physician Empathy (JSPE) and the Rathus Assertiveness Schedule (RAS) to evaluate these traits. Results reveal moderate levels of empathy and assertiveness, characterized by the recognition of emotional understanding’s importance in patient care, though practical application remains inconsistent. Assertiveness is higher in professional contexts but lower in personal boundary-setting, indicating gaps in interpersonal confidence. The study identifies no significant differences in empathy across gender, academic year, age, or college but finds that female students exhibit significantly higher assertiveness. Regression analysis shows a weak association between empathy and assertiveness, suggesting these traits develop independently and require distinct training. The findings highlight the need for structured educational interventions to bridge these gaps, such as narrative medicine, role-playing, and assertiveness workshops. Addressing cultural and academic challenges, the study underscores the importance of fostering empathetic and assertive behaviors in medical students to enhance both patient care and professional communication. This research contributes to optimizing medical education and preparing students for the complex demands of the healthcare profession.